2019
DOI: 10.13057/biodiv/d200534
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gamma rays irradiation on diversity of Musa paradisiaca var. sapientum as revealed by ISSR molecular marker

Abstract: Abstract. Due MS, Susilowati A, Yunus A. 2019. The effect of gamma rays irradiation on diversity of Musa paradisiaca var. sapientum as revealed by ISSR molecular marker. Biodiversitas 20: 1416-1422. Pisang Ambon (Musa paradisiaca var. sapientum (L.) Kunt.) is one of the horticultural commodities that have high production in Indonesia, making it a superior product. Bananas are propagated vegetatively, which hampers the production of genetic variation and requires a long generation time in the vegetative cycle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Each of the Raja Bulu banana individual in the 10 Gy gamma ray irradiation treatment (R2) showed higher total fruit weight in a single bunch than without irradiation treatment (control) (Table 2). This is supported by Due et al (2019) that gamma ray irradiation at a dose of 10 Gy showed increases in banana growth in all parameters observed when compared to controls. The highest total weight of fruit in a single bunch was found in 10 Gy gamma ray irradiation treatment, namely R2 98 sample at 4.4 kg; while the lowest total weight of fruit in one bunch was 1.37 kg in sample R2 17.…”
Section: Total Weight Of Fruit In One Bunch and Number Of Fruit Combssupporting
confidence: 64%
“…Each of the Raja Bulu banana individual in the 10 Gy gamma ray irradiation treatment (R2) showed higher total fruit weight in a single bunch than without irradiation treatment (control) (Table 2). This is supported by Due et al (2019) that gamma ray irradiation at a dose of 10 Gy showed increases in banana growth in all parameters observed when compared to controls. The highest total weight of fruit in a single bunch was found in 10 Gy gamma ray irradiation treatment, namely R2 98 sample at 4.4 kg; while the lowest total weight of fruit in one bunch was 1.37 kg in sample R2 17.…”
Section: Total Weight Of Fruit In One Bunch and Number Of Fruit Combssupporting
confidence: 64%
“…ISSR markers have been shown to reveal and produce high polymorphic alleles (Siew et al 2018;Due et al 2019). The high polymorphic allele in durian is due to the open and random cross-pollination mechanism (Handayani 2016).…”
Section: Brongkol's Superior Durian Polymorphismmentioning
confidence: 99%
“…This marker is part of a microsatellite sequence that does not code for protein (non-coding region) and comprises one, two, or three nucleotides (Ng and Tan 2015). ISSR is superior to RAPD (Cui et al 2016;Daryono et al 2019;Due et al 2019). The advantages of this marker are high reproducibility, highly polymorphic, environmentally independent, cost-effective, and do not require the entire DNA sequence to design the primer (Jia et al 2011;Thul et al 2012;Animasaun et al 2015;Sunar et al 2016;Igwe et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular techniques such as molecular markers offer an opportunity to help detect the genetic diversity within a population (Abdulhafiz et al 2018;Due et al 2019). Some previous research has shown that molecular markers RAPD (random amplified polymorphic DNA) is reliable and effective for assessing genetic diversity both within and between Coffea species (Mishra et al 2012).…”
Section: Introductionmentioning
confidence: 99%